PENGENALAN EKOSISTEM DAN SUMBERDAYA PESISIR BAGI SISWA SEKOLAH MINGGU SEKTOR LATTA JEMAAT GPM RUMAHTIGA KOTA AMBON - Manuputty, Gratia D.; Ratuluhain, Eva Susan; Noya, Yunita A (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2023)
The main coastal ecosystems are mangroves, seagrasses, and coral reefs, with various resources in them. Introduction to coastal ecosystems and their resources can be implemented early on, and this is one way to instill understanding, knowledge, and awareness about the importance of coastal ecosystems for humans. Children who are members of the Sunday School Service (SMTPI) Latta Sector of the GPM Rumahtiga Congregation are also residents of the Ambon city area who need to have responsibility for their environment from an early age. The Community Service activity was carried out on Thursday, April 20, 2023, with the target of this activity being all students and teachers of the Sunday School Service. The implementation of activities is carried out using creative learning methods using interactive media that have been prepared by the team. In practice, SMTPI students are divided into several groups according to their level which was based on the age of the child, namely the Anak Kecil (7-9 years old), Anak Tanggung (10-12 years old), and Anak Remaja (13-15 years old). The mechanism for PkM activities was divided into 3 main parts, namely socialization by applying creative learning methods, material enrichment through the lecture method, and group evaluations.